Black list : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2012)
When his name is added to a top-secret government list of individuals slated for assassination, counterterrorism operative Scot Harvath engages in a high-stakes cat-and-mouse game of survival while struggling to prevent a cataclysmic terrorist attack and learn who has framed him for treason.